Diabetes duration and thyroid stimulating hormone levels in children with type 1 diabetes mellitus - Nur Rochmah; Muhammad Faizi (Paediatrica Indonesiana, 2018)
Background Children with type 1 diabetes mellitus (T1DM) are at risk of thyroid dysfunction. An association between diabetes duration and thyroid stimulating hormone level remains inconclusive. Objective To assess for a possible association between diabetes duration and thyroid stimulating hormone levels in children with T1DM. Methods We conducted a cross-sectional study from January to June 2017 in the Pediatric Endocrine Outpatient Clinic at Dr. Soetomo Hospital. Subjects were children with T1DM aged 7 to <18 years. Exclusion criteria were children with diabetic ketoacidosis, previously diagnosed thyroid problems, and hospitalization in the pediatric intensive care unit (PICU).Â Results From the 55 regular patients in our outpatient clinic, 34 patients were included in the study. Nineteen (54.3%) subjects were male, and the overall mean age was 11.3 years. Subjects' mean duration of diabetes was 3 years and their mean thyroid stimulating hormone concentration was 3.76mIU/L. Pearson's correlation test revealed no significant association between duration of diabetes and thyroid stimulating hormone level (rs=-0.068; P=0.703). Conclusion There is no significant association between duration of diabetes and thyroid stimulating hormone levels in children with T1DM.